2008
DOI: 10.1007/s11182-008-9031-4
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed-periodic laser on RM helium and strontium transitions

Abstract: 621.375.826 Conditions of generation of a running excitation wave in the active medium of gas lasers and efficiency of the running wave application for pumping of the active medium are considered by the example of a strontium vapor laser. It is demonstrated that the running excitation wave is generated directly in the active laser medium and is supported by the energy stored in the capacitive component of the impedance of a gas-discharge tube. Generation on the self-limited (2 1 P 1 -2 1 S 0 ) transition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Lasing on three more SrI transitions at ~3 μm with pulse duration of ~50 ns delayed by ~40 ns from the onset of lasing on the above-indicated transitions was also observed during the current pulse; the mechanism of forming the inverse population on these transitions was discussed in [2]. Under conditions of discharge excitation close to those reported in [1], lasing on the r-m transition of the HeI atom at λ = 2.06 μm and on several NeI atomic transitions in the wavelength range 1.08-1.52 μm was excited in [3] in the mixture of neon with helium (at a total pressure of ~200 mm Hg). Lasing on HeI and NeI lines as well as on SrI and SrII lines was observed during the current pulse.…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…Lasing on three more SrI transitions at ~3 μm with pulse duration of ~50 ns delayed by ~40 ns from the onset of lasing on the above-indicated transitions was also observed during the current pulse; the mechanism of forming the inverse population on these transitions was discussed in [2]. Under conditions of discharge excitation close to those reported in [1], lasing on the r-m transition of the HeI atom at λ = 2.06 μm and on several NeI atomic transitions in the wavelength range 1.08-1.52 μm was excited in [3] in the mixture of neon with helium (at a total pressure of ~200 mm Hg). Lasing on HeI and NeI lines as well as on SrI and SrII lines was observed during the current pulse.…”
Section: Introductionmentioning
confidence: 54%
“…We note that lasing on lines of the buffer gas at sufficiently high pressure in the He-Ne-Sr laser can be excited only in the presence of the Sr atoms delivered from the hot walls of the gas-discharge tube (GDT). This conclusion was made by Chebotarev et al [4] who demonstrated that under conditions of discharge excitation close to those of [1][2][3], the presence of the Sr atoms with the concentration ~4·10 14 cm -3 prevents contraction of the pulse-periodic discharge inevitable for sufficiently high pressure in the hot GDT.…”
Section: Introductionmentioning
confidence: 59%
“…In the case where the second and the third circuits are eliminated from the pump system of the active laser medium, using, say, the self-capacitance of the gas-discharge tube as a storage capacitor, an RM laser efficiency of ~10% (~6-8% for a strontium-vapor laser) can be obtained. A laser efficiency as high as this suggests that the average lasing power can be increased by an order of magnitude as compared to the currently available power level and multiple-wavelength lasers can be developed [24]. This shows good promise for development of lasers on RM transitions of metal atoms.…”
Section: Discussionmentioning
confidence: 95%